Determination of room impulse response for synthetic data acquisition - Moquin, Philippe; Venalainen, Kevin; Florencio, Dinei; dinei (2014)
Our proposed solution is to measure room impulse response and convolve the test vectors to synthesise measured data to the fidelity required to accurately test ASR.